1996
DOI: 10.1006/viro.1996.0583
|View full text |Cite
|
Sign up to set email alerts
|

The Mumps Virus SH Protein Is a Membrane Protein and Not Essential for Virus Growth

Abstract: By immunoprecipitation analysis using antisera against oligo peptides synthesized based on the deduced N-terminal and C-terminal amino acid sequences of the SH proteins of the mumps virus, the SH protein was detected in mumps virus-infected cells. The SH protein expressed from cDNA by the vaccinia-T7 expression system was recovered in the membrane fraction. Association of the SH protein with the membrane was resistant to high salt, EDTA, and alkaline treatment but sensitive to detergents. Indirect immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 3 publications
3
52
0
Order By: Relevance
“…Staining against protein disulfide isomerase (PDI) demonstrated that the SH protein was localized in the ER (Fig. 3b), as reported previously by Takeuchi et al (1996). When pHA-SH wt and pMyc-A1Up were co-expressed, SH was partially redistributed to co-localize with A1Up and the 20S proteasome in the aforementioned punctate structures (Fig.…”
Section: Subcellular Localization Of A1up and Shsupporting
confidence: 80%
See 1 more Smart Citation
“…Staining against protein disulfide isomerase (PDI) demonstrated that the SH protein was localized in the ER (Fig. 3b), as reported previously by Takeuchi et al (1996). When pHA-SH wt and pMyc-A1Up were co-expressed, SH was partially redistributed to co-localize with A1Up and the 20S proteasome in the aforementioned punctate structures (Fig.…”
Section: Subcellular Localization Of A1up and Shsupporting
confidence: 80%
“…Recently a new genotype, M, was described (Santos et al, 2008). The SH (small hydrophobic) protein of MuV is expressed in MuV-infected cells but is not a constituent part of the virion (Takeuchi et al, 1996). SH is apparently non-essential for viral replication in cell culture, since the growth rate of cell culture-adapted strain Enders, which does not express the SH protein, is not restricted compared with wild-type MuV strains (Afzal et al, 1990;Takeuchi et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The SH gene of MuV is 316 nucleotides long and encodes a protein of 57 amino acids that is detected in MuV-infected cells (13). The SH gene is the most heterogeneous in comparison with any other region of the *Address correspondence to Dr. Kazue Uchida, Virus Division, Saitama Institute of Public Health, Kamiokubo 639-1, Saitama, Saitama, 338-0824, Japan.…”
mentioning
confidence: 99%
“…Fax: +81-48-840-1041. E-mail: virus31 @f3.dion.ne.jp 851 MuV genome; therefore it is useful for the identification and classification ofMuV isolates (12)(13)(14). Orvell et al analyzed the SH gene nucleotide sequences of MuV isolates from USA, Europe, and Japan and suggested that these strains formed five genotypes A to E (8).…”
mentioning
confidence: 99%
“…F and HN, integral membrane proteins which project from the surface of the virion, are involved in virus attachment and entry of cells. The SH and M proteins are also membrane associated (18,38).…”
mentioning
confidence: 99%